Ijtihad, Mujtihad, dan Muqolid Dalam Pengembangan Hukum Islam - Henny Putri; Nabilla Rasya Putri (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study aims to analyze the concept of Ijtihad, Mujtihad, and muqollid in the development of Islamic law. The development of Islamic law cannot be separated from Ijtihad, Mujtihad and Muqollid. Ijtihad is an intellectual effort of an Islamic legal expert in exploring and establishing the law from all its main sources, namely the Qur’an and Hadith, through rational and conceptual reasoning methods in this process Mujtahid plays a role as the main subject who has deep scientific competence. The ability to istinbath law, as well as high moral integrity. Meanwhile, Muqollid is a party who follows the opinions or results of the ijtihad of the Mujtahids without conducting legal reasoning independently.The relationship between Mujtihad and Muqollid forms an epistemological structure that maintains the balance and stability of Islamic law amidst changing times. Therefore, the understanding of Ijtihad, Mujtihad, and Muqollid is crucial for understanding how Islamic law aligns with the Qur’an and Hadith, and how Islamic law is developed dynamically without losing its normative foundation. This understanding emphasizes that Ijtihad is the adaptation of Islamic teachings to the changing times and the needs of the community. A Mujtihad is someone who possesses a high level of scholarly capacity in sharia, Arabic, Usul al-Fiqh, and tafsir, enabling them to conduct ijtihad. A Muqollid follows the Mujtihad’s opinion, as they are unable to conduct ijtihad themselves; they instead refer to the results of prior ijtihad from scholars or madhhabs. In The development of Islamic law in these three are is interconnected:Ijtihad, Mujtihad and muqollid.